Determinants of stock market co-movements between Pakistan and Asian emerging economies - Muhammad Aamir; Syed Zulfiqar Ali Shah (Journal of Risk and Financial Management, 2018)
This study analyzes the determinants of stock market co-movement between Pakistan and Asian emerging economies for the period 2001 to 2015. Augmented Dickey and Fuller (ADF) and Philips-Perron (PP) tests are applied to check co-integration between their stock markets. Results of this study reveal that there is long-term integration between the stock market of Pakistan and the stock markets of China, India, Indonesia, Korea, Malaysia and Thailand. This study reports the driving forces of the co-movement between the Pakistan and Asian emerging markets where co-integration is found. Results of the panel data reveal that there are significant underlying forces of integration between Pakistan and each Asian emerging stock market. The findings of this study have significant implications for policy makers in Pakistan who are designing strategies for macroeconomic harmonization and stability of the country's economy against financial shocks.
Keywords: 330; stock market co-movement; portfolio diversification; economic integration; financial crisis